Alcohol use and alcohol use disorder differ in their genetic relationships with PTSD: A genomic structural equation modelling approach. (1st May 2022) - Bountress, Kaitlin E.; Brick, Leslie A.; Sheerin, Christina; Grotzinger, Andrew; Bustamante, Daniel; Hawn, Sage E.; Gillespie, Nathan; Kirkpatrick, Robert M.; Kranzler, Henry; Morey, Rajendra; Edenberg, Howard J.; Maihofer, Adam X.; et al.
Abstract: Purpose: Posttraumatic Stress Disorder (PTSD) is associated with increased alcohol use and alcohol use disorder (AUD), which are all moderately heritable. Studies suggest the genetic association between PTSD and alcohol use differs from that of PTSD and AUD, but further analysis is needed. Basic procedures: We used genomic Structural Equation Modeling (genomicSEM) to analyze summary statistics from large-scale genome-wide association studies (GWAS) of European Ancestry participants to investigate the genetic relationships between PTSD (both diagnosis and re-experiencing symptom severity) and a range of alcohol use and AUD phenotypes. Main findings: When we differentiated genetic factors for alcohol use and AUD we observed improved model fit relative to models with all alcohol-related indicators loading onto a single factor. The genetic correlations (rG) of PTSD were quite discrepant for the alcohol use and AUD factors. This was true when modeled as a three-correlated-factor model (PTSD-AUD rG:.36, p < .001; PTSD-alcohol use rG: −0.17, p < .001) and as a Bifactor model, in which the common and unique portions of alcohol phenotypes were pulled out into an AUD-specific factor (rG with PTSD:.40, p < .001), AU-specific factor (rG with PTSD: −0.57, p < .001), and a common alcohol factor (rG with PTSD:.16, NS). Principal conclusions: These results indicate the genetic architecture of alcohol use and AUD are differentially associated with PTSD. When the portions of variance unique to alcohol use and AUD are extracted, their genetic associations with PTSD vary substantially, suggesting different genetic architectures of alcohol phenotypes in people with PTSD. Highlights: Using genomic Structural Equation Modeling (gSEM), a Bifactor model fit best. The genetic correlation between PTSD and AUD was significant and positive. The genetic correlation between PTSD and alcohol use was significant and negative. The genetic correlation between PTSD and the general alcohol factor was NS.